The impact of DECISION+2 on patient intention to engage in shared decision making: secondary analysis of a multicentre clustered randomized trial. (7th July 2014) - Couët, Nicolas; Labrecque, Michel; Robitaille, Hubert; Turcotte, Stéphane; Légaré, France
Abstract: Background: Training health professionals in shared decision making (SDM) may influence their patients' intention to engage in SDM. Objective: To assess the impact of DECISION+2, a SDM training programme for family physicians about the use of antibiotics to treat acute respiratory infections (ARIs), on their patients' intention to engage in SDM in future consultations. Design: Secondary analysis of a multicentre clustered randomized trial. Setting and participants: Three hundred and fifty‐nine patients consulting family physicians about an ARI in nine family practice teaching units (FPTUs). Intervention: DECISION+2 (two‐hour online tutorial, two‐hour workshop, and decision support tools) was offered in the experimental group (five FPTUs, 162 physicians, 181 patients). Usual care was provided in the control group (four FPTUs, 108 physicians, 178 patients). Outcome measure: Change in patients' intention scores (range −3 to +3) between pre‐ and post‐consultation. Results: The mean ± SD [median] scores of intention to engage in SDM were high in both study groups before consultation (DECISION+2 group: 1.4 ± 1.0 [1.7]; control group: 1.5 ± 1.1 [1.7]) and increased in both groups after consultation (DECISION+2 group: 2.1 ± 1.1 [2.7]; control group: 1.9 ± 1.2 [2.3]). Change of intention, classified as either increased, stable or decreased, was not statistically associated with the exposure to the DECISION+2 programme after adjusting for the cluster design (proportional odds ratio = 1.5; 95% confidence interval = 0.8–3.0). Conclusion: DECISION+2 had no significant impact on patients' intention to engage in SDM for choosing to use antibiotics or not to treat an ARI in future consultations. Patient‐targeted interventions may be necessary to achieve this purpose.